2016
DOI: 10.1021/acsomega.6b00351
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Route to the Fabrication of CH3NH3PbI3 Perovskite Thin Films by Electrodeposition and Vapor Conversion

Abstract: Hybrid halide perovskite thin films are applicable in a wide range of devices such as light-emitting diodes, solar cells, and photodetectors. The optoelectronic properties of perovskites together with their simple and inexpensive film deposition methods make these materials a viable alternative to established materials in these devices. However, the potential of perovskite materials is compromised by the limitations of the existing deposition methods, which suffer from trade-off among suitability for large-sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 61 publications
3
46
0
Order By: Relevance
“…Figure 2 shows the different stages in CsPbBr 3 formation from bare FTO. In contrast to a previous study, [48] where well-covered films were obtained only after 500 s, we accomplished a very homogeneous and well-covering PbO 2 film after 280 s of reaction with the same current density. This is probably due to the positive effect of the activation protocol with HNO 3 on the FTO pieces before electrodeposition.…”
Section: Structural Propertiesmentioning
confidence: 73%
See 4 more Smart Citations
“…Figure 2 shows the different stages in CsPbBr 3 formation from bare FTO. In contrast to a previous study, [48] where well-covered films were obtained only after 500 s, we accomplished a very homogeneous and well-covering PbO 2 film after 280 s of reaction with the same current density. This is probably due to the positive effect of the activation protocol with HNO 3 on the FTO pieces before electrodeposition.…”
Section: Structural Propertiesmentioning
confidence: 73%
“…(1)], galvanostatic electrodeposition of PbO 2 over FTO has proven useful to prepare MAPI. After PbO 2 films were formed and characterized, their conversion to PbBr 2 was designed in a similar way as reported by Kemel et al [48] They reported for the first time the chemical reduction of PbO 2 films to PbI 2 under exposure to HI vapors.…”
Section: Electrochemical Deposition Of Pbo 2 On Fto and Its Conversiomentioning
confidence: 95%
See 3 more Smart Citations